Subcutaneous anakinra in the management of refractory MIS-C in France - Dusser, Perrine; Belot, Alexandre; Bajolle, Fanny; Kevorkian-Verguet, Charlotte; Meinzer, Ulrich; Huet, Frédéric; Tiriau, Soizic; Kone-paut, Isabelle (Frontiers in Pediatrics, 2024)
Introduction: Multisystemic inflammatory syndrome in children (MIS-C) is a therapeutic emergency and can lead to myocardial dysfunction (17-75%) and heart failure (52%-53%). Immunoglobulins (IVIG) and corticosteroids (CST) have been validated for the management of this condition. Recent reports suggest that IL-1 receptor antagonist, namely anakinra, may be a valuable add-on to COVID-19 treatment for refractory patients. The purpose of this study was to describe the clinico-biological characteristics of patients treated with anakinra as well as the efficacy and safety of subcutaneous anakinra therapy in this condition. Methods: Prospective multicentre study of children hospitalized for MIS-C between March 2020 and September 2022, from 23 international paediatric centres, followed for a mean duration of 3.072 ± 3.508 months. Patient data were extracted from the Juvenile Inflammatory Rheumatism (JIR) cohort. Clinico pathological characteristics, cardiac ultrasound data and adverse events were reported in patients receiving anakinra. Results: Of 470 children admitted with MIS-C, 18 French patients (50% girls) with a mean age of 10.06 ± 3.9 years were treated with subcutaneous anakinra. Anakinra was used in two situations, macrophage activation syndrome (MAS) (4 patients) and heart failure (14 patients) with a median LVEF of 39.5% [30% - 45%]. The average dose of anakinra received was 2.53 ±1.3 mg/kg/day for a median duration of 3 days. Prior to introduction, 78% (n=14/18) of the patients had received CST and 56% (n=10/18) had received IVIG. Only 2 patients received IVIG alone and 6 received CST alone plus anakinra. In 10% of cases, IVIG was poorly tolerated from a cardiovascular point of view and was discontinued. Transient elevations in serum transaminases was noted in 4 patients on anakinra without the need for treatment or dose modification. In all patients, rapid (48 hours) improvement in myocardial function was observed (LVEF>55%) with a concomitant significant decrease in myocardial enzymes (p<0.05). All patients survived with complete recovery of cardiac function without sequelae. Conclusions: Subcutaneous anakinra appears to be a safe and effective treatment for the management of heart failure or MAS in MIS-C patients. The value of IVIG in these two situations remains to be reviewed.